2018
DOI: 10.4103/ija.ija_752_17
|View full text |Cite
|
Sign up to set email alerts
|

Role of dexmedetomidine as an anaesthetic adjuvant in breast cancer surgery as a day-care procedure: A randomised controlled study

Abstract: Background and Aims:Breast cancer surgery can be carried out as day-care procedure to increase patient turnover, decrease disease progression and financial burden. The present study was carried out to assess the role of dexmedetomidine in breast cancer surgery as a day-care procedure.Methods:This prospective randomised, double-blind study was carried out on 100 patients screened for day-care breast cancer surgery. They were divided into two groups of 50 each; who received either normal saline (Group NS) or 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Dexmedetomidine is a highly selective α2 adrenergic receptor agonist, which has the advantages of rapid onset of action, short duration of action, sedative and analgesic effects, and no respiratory depression, and is a widely used anesthesia adjuvant drug ( 9 , 10 ). In this study, we found that the anesthesia time, operation time, and blood loss during the operation did not increase in the research group with additional dexmedetomidine for anesthesia, indicating that dexmedetomidine does not affect the surgical process of patients undergoing MRM for breast cancer, which is consistent with the results in the study by Das et al ( 21 ). Das et al found that the addition of dexmedetomidine can not only significantly reduce the consumption of anesthetics in patients undergoing MRM for breast cancer, but also significantly shorten the postoperative breathing satisfaction time, eye opening time and extubation time.…”
Section: Discussionsupporting
confidence: 91%
“…Dexmedetomidine is a highly selective α2 adrenergic receptor agonist, which has the advantages of rapid onset of action, short duration of action, sedative and analgesic effects, and no respiratory depression, and is a widely used anesthesia adjuvant drug ( 9 , 10 ). In this study, we found that the anesthesia time, operation time, and blood loss during the operation did not increase in the research group with additional dexmedetomidine for anesthesia, indicating that dexmedetomidine does not affect the surgical process of patients undergoing MRM for breast cancer, which is consistent with the results in the study by Das et al ( 21 ). Das et al found that the addition of dexmedetomidine can not only significantly reduce the consumption of anesthetics in patients undergoing MRM for breast cancer, but also significantly shorten the postoperative breathing satisfaction time, eye opening time and extubation time.…”
Section: Discussionsupporting
confidence: 91%
“…One such system would be the mucosal atomization device nasal spray that was used in a previous study to deliver intranasal dexmedetomidine during third molar extraction (16). Third, although the results of the present study together with previous study (42) indicated the efficacy and safety of intranasal dexmedetomidine administration during breast lumpectomy, future studies need to be conducted to focus on the safety in a larger sample size. Fourth, individual differences in drug tolerance may also provide bias since the time point for surgery was 45 min after intranasal dexmedetomidine was selected according to previous studies (14,(28)(29) instead of plasma concentration.…”
Section: Discussionmentioning
confidence: 75%
“…These effects might be attributed to opioid-related side effects postoperatively. The study showed that dexmedetomidine did not require rescue analgesia within two hours of the procedure, and 88% patients undergoing modified radical mastectomy or breast conservative surgery could be discharged on the same day [ 48 ]. The use of dexmedetomidine as an adjuvant in ESPB may also reduce postoperative hospital stays compared to adjuvant dexamethasone administration.…”
Section: Discussionmentioning
confidence: 99%